PENINGKATAN PENGELOLAAN USAHA HIMPUNAN WANITA PENYANDANG DISABILITAS MELALUI PELATIHAN PERANCANGAN BISNIS DAN STRATEGI PROMOSI - Ratu Eva Febriani; Purmini Purmini; Bambang Agoes Hermanto (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
People with disabilities are a vulnerable group in society, especially women. The marginalization of people with disabilities makes it difficult for them to carry out economic activities to support their daily needs. In Bengkulu City, women with disabilities gather in the Association of Indonesian Women with Disabilities (HWDI). This organization functions to accommodate disabled women in Bengkulu City to become economically independent. Several types of businesses have been developed by this organization, but business development has not been able to improve members' welfare. Therefore, improving HWDI business management is important in supporting the inclusion and empowerment of women with disabilities. The method used in this activity is the counselling method. This activity aims to improve the skills and knowledge of HWDI members in managing their businesses effectively and sustainably. The results of the activity show that there is a change in mindset in running a business, there is an interest in improving business management and improving product packaging to make it more attractive and they are willing to try a different approach to marketing products.